Does Organizational Climate Affect Innovative Work Behaviour? A Study among Employees of F&B Medium Sized Enterprises - Tou, Yee Hua; Abdullah, Nor Hazana (Research in Management of Technology and Business, 2021)
Innovative work behaviour plays an important role in an organization. However, the level of innovative work behaviour in Malaysia is only moderate and need to be improved. The objective of this study is to determine the relationship between organizational climate and its components (mission and purpose, feedback, teamwork, communication, compensation, fairness and security, meaningfulness) with innovative work behaviour among employees of F&B medium sized enterprises. This research were conducted in Johor, Selangor, Penang, Kuala Lumpur and Perak. This was a quantitative study and where questionnaires were used to collect data. The data were analysed using descriptive analysis and correlation analysis. The findings showed that the relationship between organizational climate and its components (mission and purpose, feedback, teamwork, communication, compensation, fairness and security, meaningfulness) with innovative work behaviour among employees of F&B medium sized enterprises were significant. Empirically, this study contributes to the knowledge reservoir on area of innovative work behavior and organizational climate. It could become the basis for future research and development of robust theories on innovative work behavior.